ventral veinless, a POU domain transcription factor, regulates different transduction pathways required for tracheal branching in Drosophila. - Llimargas, M.; Casanova, J. (Development, 1997)
Cell migration is an important step in a variety of developmental processes in many multicellular organisms. A particularly appropriate model to address the study of cell migration is the tracheal system of Drosophila, whose formation occurs by migration and fusion from clusters of ectodermal cells specified in each side of ten embryonic segments. Morphogenesis of the tracheal tree requires the activity of many genes, among them breathless (btl) and ventral veinless (vvl) whose mutations abolish tracheal cell migration. Activation of the btl receptor by branchless (bnl), its putative ligand, exerts an instructive role in the process of guiding tracheal cell migration. vvl has been shown to be required for the maintenance of btl expression during tracheal tree formation. Here we show that, in addition, vvl is independently required for the specific expression in the tracheal cells of thick veins (tkv) and rhomboid (rho), two genes whose mutations disrupt only particular branches of the tracheal system. Indeed, we show that expression in the tracheal cells of an activated form of tkv, the putative decapentaplegic (dpp) receptor, is able to induce shifts in their migration, asserting the role of the dpp pathway in establishing the branching pattern of the tracheal tree. In addition, by ubiquitous expression of the btl and tkv genes in vvl mutant embryos we show that both genes contribute to vvl function. These results indicate that through activation of its target genes, vvl makes the tracheal cells competent to further signalling and suggest that the btl transduction pathway could collaborate with other transduction pathways also regulated by vvl to specify the tracheal branching pattern.